2015
DOI: 10.1002/2014jd022675
|View full text |Cite
|
Sign up to set email alerts
|

Rocky Mountain National Park reduced nitrogen source apportionment

Abstract: Excess wet and dry deposition of nitrogen-containing compounds are a concern at a number of national parks. The Rocky Mountain Atmospheric Nitrogen and Sulfur Study Part II (RoMANS II) campaign was conducted from November 2008 to November 2009 to characterize the composition of reactive nitrogen and sulfur deposited in Rocky Mountain National Park (RMNP). RoMANS II identified reduced nitrogen as the major contributor to reactive nitrogen deposition in RMNP, making up over 50% of the total. Motivated by this fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 38 publications
8
38
0
Order By: Relevance
“…This is consistent with the spatial distributions of the emissions of NH 3 compared to those of NO x surrounding the park. The high sensitivity of reduced Nr to sources west of RM in California and Idaho agrees with other recent studies (Benedict et al, 2013b;Malm et al, 2013;Thompson et al, 2015).…”
Section: Spatial and Sectoral Footprints Of Nr Depositionsupporting
confidence: 80%
See 2 more Smart Citations
“…This is consistent with the spatial distributions of the emissions of NH 3 compared to those of NO x surrounding the park. The high sensitivity of reduced Nr to sources west of RM in California and Idaho agrees with other recent studies (Benedict et al, 2013b;Malm et al, 2013;Thompson et al, 2015).…”
Section: Spatial and Sectoral Footprints Of Nr Depositionsupporting
confidence: 80%
“…Still, adequate model performance in other seasons and locations suggests a considerable contribution of dry deposition of NH 3 in some locations and seasons, consistent with Schwede and Lear (2014). A significant fraction of Nr deposition in the central mountain region (including Rocky Mountain National Park) is estimated to be in the form of reduced nitrogen, similar to several other recent studies (Benedict et al, 2013b;Malm et al, 2013;Thompson et al, 2015), although such estimates are sensitive to model uncertainties in NH 3 emissions and modeled NO − 3 . The spatial and sectoral distribution of annual Nr deposition sources are investigated using the adjoint of GEOSChem.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…To assess the extent of boundary layer mixing and dilution, potential temperature profiles measured by the Pennsylvania State University NATIVE integrated ozonesonde (A. M. Thompson et al, 2015), launched near Platteville (40 • 10 53 N, 104 • 43 36 W) during NASA DISCOVER-AQ, were examined. Except for 26 July when at 12:00 MST the boundary layer (BL) height was observed to be at 2200 m a.s.l., midday BL heights on other days were consistently at ∼ 3400-3600 m a.s.l.…”
Section: Data Processingmentioning
confidence: 99%
“…Recent studies have shown O & G emissions of non-methane hydrocarbons (NMHC) such as short-chain alkanes (C 1 -C 4 ) and alkenes act as precursors to ozone (Pétron et al, 2012(Pétron et al, , 2014Edwards et al, 2013;Gilman et al, 2013;Karion et al, 2013), but the potential for these emissions to contribute to primary and secondary OA in the region has not been investigated. Additionally, agricultural practices and powerplant operations in the greater Colorado region contribute to visibility impairment and ecosystem degradation through formation of secondary nitrate and sulfate-containing compounds (Williams and Tonnessen, 2000;Nanus et al, 2003;Blett et al, 2004;Burns, 2004;Boy et al, 2008;Malm et al, 2013;Mast and Ely, 2013; T. M. Thompson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%